Ethylene Evaporation Rate Analysis in the Storage Tank and Boil-Off Gas Dispersion: Case Study in PT Lotte Chemical Titan Nusantara - Rachmaniah, Orchidea; Lazuardi, Khoir; Rizky, Ajeng Nina; Al-Mauhub, Rijaalul Mulhim; Faridsyah, Ibnu; Cahyadi, Bagus (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
As a primary raw material at PT Lotte Chemical Titan Nusantara (LCTN), ethylene storage is 12,000 tons in icy conditions (- 103.6 °C and 40-80 mbarg) before processing into polyethylene. Ethylene evaporation is inevitable. Therefore, the proper handled of ethylene needs to be settled. The evaporation rate or Boil-Off Rate (BOR) of ethylene is predicted to be 0.0705-0.0730% vol/day, and the Boil-Off Gas (BOG) is 9.41-9.76 tons per day (at 21-40 °C and a tank liquid level of 15.41 meters, approx. 52.51% volume of tank). The BOR is a predicted value of the percentage of volume evaporated daily. When the liquid level is increased, the BOR rate will also be increased. The size of any leaks dramatically impacts the gas dispersion radius. A leak with a 10 mm size at wind speeds of 5 and 10 km/hr resulted in the radius distance of BOG dispersion being 8.2 and 7.7 m, respectively. When the leak hole is ten times bigger, ca. 100 mm, the radius is eight times wider. Fortunately, gas releases happen well above ground level (15.5 meters), causing the cloud to rise, keeping personnel safe. Too low liquid levels ramp up evaporation, risking shortages, while overfilling increases BOG, raising the chance of spills and safety hazards. Hence, managing these variables is crucial to keep operations smooth and safe.